PENGELOLAAN ZAKAT DI BADANG AMIL ZAKAT NASIONAL KABUPATEN MAMUJU - Aras. P, Muh; Mappamiring, Mappamiring; Umar, M Amin (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThis study aims to determine the management of zakat in the National Amil Zakat Agency of Mamuju Regency. The type of research used is a qualitative research method with a descriptive type of research. Data collection techniques using observation, interviews, and documentation. The results of the study show that 1) planning time targets, assumptions, time frames and program directions, as outlined in the Budget Work Plan (RKA), 2) organizing by screening from sub-district to sub-district and mosques, 3) movement by applying operational principles, and having working relationship with UPZ, 4) control, is a supervisory activity from the audited party with the aim of supervising the work programs and processes carried out by BAZNAS to achieve zakat objectives, and to avoid deviations in zakat management.Keywords: Management, zakat